Two simple and inexpensive methods for preparing DNA suitable for digital PCR from a small number of cells in 96‐well plates. Issue 1 (5th August 2020) - Zou, Ziang; Guo, Linna; Ahmadi, Parimah; Hartjen, Philip; Gosau, Martin; Smeets, Ralf; Kluwe, Lan
Abstract: Background: Although DNA of high quality can be easily prepared from cultured cells with commercially available kits, many studies involve a large number of samples which increases the cost drastically. We optimized two simple and inexpensive methods for preparing DNA suitable for digital PCR from a small number of cells directly from wells of 96‐well plates. Methods: Cells (number: 10 3 ‐10 4 ) were lysed with a Direct PCR ® lysis buffer or a 10% Chelex100® solution. The lysates were further purified and concentrated by means of DNA precipitation with a blue‐colored glycogen as a carrier. PCR and digital PCR were used to evaluate the efficiency of the two methods. Results: For 1000 cells from one primary culture and two tumor cell lines, DNA was reproducible and obtained with recovery rate (obtained/expected amount of DNA) in the range of 50%‐90% as measured by the fluorometer dyes instrument Qubit. Using 8 out of a total of 10 µL DNA solution for 1000 cells, both conventional PCR and digital PCR were successful. For digital PCR, more than 1600 positive droplets were obtained for DNA from 1000 cells using the Direct PCR ® method, corresponding to a yield efficiency of approximately 80%. Further reducing the number of cells down to 100 would be possible with 160 positive droplets expected. Both reagents are inexpensive (0.08€/sample). Conclusions: Two methods are efficient, especially the Direct PCR ® reagent‐based method provides a simple and inexpensive method for preparing DNA suitable for digital PCR from small number of cells. Abstract : With commercially available kits, DNA of high quality can be easily prepared from cultured cells. However, many studies involve a large number of samples which increases the cost drastically. In addition, a limited amount of each sample often is also a challenge. We optimized two simple and inexpensive methods for preparing DNA suitable for digital PCR from a small number of cells directly from wells of 96‐well plates. Using 8 out of the total of 10µl DNA solution for 1000 cells, both conventional PCR and digital PCR were successful. For digital PCR, more than 1600 positive droplets were obtained for DNA from 1000 cells using the Direct PCR® method, corresponding to a yield efficiency of approximately 80%.